Persian Gulf 2024–25 - Kumaraswamy, P. R. author. aut Link
XXIV, 456 p. 2 illus., 1 illus. in color.
Keywords: The Persian Gulf 2024-25, part of the annual Persian Gulf Series published by MEI@ND, offers a comprehensive and systematic analysis of important political, foreign policy, security, economic and societal developments in the nine Gulf countries, namely Bahrain, Iran, Iraq, Kuwait, Oman, Qatar, Saudi Arabia, the United Arab Emirates and Yemen as well as the Gulf Cooperation Council (GCC), and focuses on the developments of 2023 and 2024. It captures the important political, diplomatic, economic, strategic, cultural and expatriate-related developments between India and the regional countries in 2023 and 2024, and offers concise policy recommendations for the Indian industries, businesses, defence and security establishment and the Government of India. The book will interest universities and colleges with departments on international relations and foreign policy, as well as strategic and research institutions and think tanks as well as governments engaged with Persian Gulf countries. P. R. Kumaraswamy is a Professor of contemporary Middle East at Jawaharlal Nehru University (JNU), New Delhi. Sameena Hameed is Professor in Middle Eastern Studies at Jawaharlal Nehru University (JNU), New Delhi. Md. Muddassir Quamar is Associate Professor in Middle Eastern Studies at Jawaharlal Nehru University (JNU), New Delhi.